Evaluation of First-Week Fluid Intake and Maximal Weight Loss Percentage with In-Hospital Adverse Outcomes Among Moderately and Very Preterm Newborns in Ethiopia - Gregory C. Valentine; Tessa Rue; Olivia C. Brandon; Krystle M. Perez; Thomas R. Wood; Sharla Rent; Gal Barbut; Merhawit Abadi; Redeat Workneh; Gesit Metaferia; Mahlet Abayneh (Children)
Background/Objective: We sought to address ongoing gaps in understanding the relationship between first-week percent maximal weight loss (MWL) and average first-week total fluid intake (TFI), enteral intake, and parenteral intake among premature newborns with adverse in-hospital outcomes born in low- and middle-income countries (LMICs). Methods: We evaluated newborns born <34 weeks gestation or <1500 g who survived at least 7 days at the St. Paul’s Hospital Millennium Medical College (SPHMMC) neonatal intensive care unit in Ethiopia. We performed univariate and multivariate regression models analyzing the first-week MWL, average TFI, parenteral, and enteral intake and their relationships with adverse in-hospital outcomes. Results: Among N = 490 moderately and very preterm newborns, multivariate regression models demonstrated that >13% MWL was associated with significantly increased odds of suspected necrotizing enterocolitis (NEC), culture-positive sepsis, retinopathy of prematurity (ROP), and a longer length of stay (LOS). An average enteral intake of >60 mL/kg/day was significantly associated with reduced odds of all-cause mortality, suspected NEC, culture-positive sepsis, ROP, and a shorter LOS, whereas an average parenteral intake of >60 mL/kg/day was associated with increased odds of in-hospital mortality, culture-positive sepsis, ROP, and a longer LOS. Conclusions: In moderately and very preterm neonates in an LMIC setting, >13% MWL is associated with adverse health outcomes. Increasing the average parenteral intake over the first week after birth among moderately and very preterm neonates is significantly associated with adverse in-hospital outcomes whereas increasing the average enteral intake is associated with improved outcomes.